2019
DOI: 10.3390/ijms20020261
|View full text |Cite
|
Sign up to set email alerts
|

New Oxidovanadium(IV) Coordination Complex Containing 2-Methylnitrilotriacetate Ligands Induces Cell Cycle Arrest and Autophagy in Human Pancreatic Ductal Adenocarcinoma Cell Lines

Abstract: Pancreatic cancer is characterized by one of the lowest five-year survival rates. In search for new treatments, some studies explored several metal complexes as potential anticancer drugs. Therefore, we investigated three newly synthesized oxidovanadium(IV) complexes with 2-methylnitrilotriacetate (bcma3−), N-(2-carbamoylethyl)iminodiacetate (ceida3−) and N-(phosphonomethyl)-iminodiacetate (pmida4−) ligands as potential anticancer compounds using pancreatic cancer cell lines. We measured: Cytotoxicity using 3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 66 publications
5
18
0
1
Order By: Relevance
“…These studies highlight the importance of the chemical form of vanadium-based complexes in determining their mechanism of action. In our team study, the oxidovanadium complex containing quinolinium cation (66) induced cycle arrest in the G2/M phase with simultaneous triggering of the p53/p21 pathway in pancreatic cancer cell lines [79]. Induction of the p53/p21 pathway was also determined in cervical cancer cells treated by vanadium complexes of nicotinoyl hydrazine (67 and 68) [80].…”
Section: Cell Cycle Arrestmentioning
confidence: 93%
See 1 more Smart Citation
“…These studies highlight the importance of the chemical form of vanadium-based complexes in determining their mechanism of action. In our team study, the oxidovanadium complex containing quinolinium cation (66) induced cycle arrest in the G2/M phase with simultaneous triggering of the p53/p21 pathway in pancreatic cancer cell lines [79]. Induction of the p53/p21 pathway was also determined in cervical cancer cells treated by vanadium complexes of nicotinoyl hydrazine (67 and 68) [80].…”
Section: Cell Cycle Arrestmentioning
confidence: 93%
“…Furthermore, we have determined that vanadium complexes with phenanthroline (45,47) also trigger the necroptosis pathway in a human pancreatic ductal adenocarcinoma cell line [52]. In another study, we have found that an oxidovanadium complex with quinolinium cation (66) induced autophagic process in pancreatic cancer cells with simultaneous increase in the RAGE protein level [79]. Autophagy was also detected in vanadium-treated (90) breast cancer cells [101].…”
Section: Programed Cell Deathmentioning
confidence: 95%
“…In addition to the possibilities inherent in combination therapy, pre-clinical studies continue to provide us with new chemical moieties which are potentially promising in PDAC therapy. These include metal moeities such as oxidovanadium (IV) coordination complexes which have been shown to be toxic to PDAC cell lines, but not non-tumor human immortalized pancreas duct epithelial cells [55]. Interestingly, these compounds induce, rather than inhibit autophagy, so their anti-proliferative activity may be exerted via other mechanisms, such as increased reactive oxygen species generation [55].…”
Section: Autophagy As a Therapeutic Target For Pancreatic Cancermentioning
confidence: 99%
“…In addition, they hypothesized (on the basis of studies conducted by other researchers) that the VOL(bipy) complex may be modified by coapplication with an antioxidant to be safer than the administration thereof alone. In turn, a study reported by Kowalski et al [164] revealed that oxidovanadium(IV) coordination complexes containing a 2-methylnitrilotriacetate ligand are good candidates for preclinical development of novel anticancer drugs targeting pancreatic cancer. As suggested, the molecular mechanisms of cytotoxicity of these complexes were dependent on generation of ROS and cell cycle arrest in the G2/M phase with simultaneous activation of the p53/p21 pathway.…”
Section: Mechanisms Of the Anti-neoplastic Activity Of Vanadium: A Sumentioning
confidence: 99%